2008
DOI: 10.4103/0301-4738.43383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological features of posttraumatic iris cyst

Abstract: Iris cyst excision involves complex surgical maneuvers and may have a variable visual outcome depending upon preexisting and postoperative complications. Hereby, we report a case series of 10 eyes from which posttraumatic iris cysts were excised and proven histopathologically. Histopathology records were reviewed. Data regarding patient profile, clinical profile, surgical details, treatment outcomes and follow-up were reviewed. Outcome measures were defined as recurrences, visual acuity and number of other sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
1
Order By: Relevance
“…The follow-up of our case is considerably longer than previous studies reporting iris lesions. For example, mean follow-up was 2.36 years in one study [6] and up to 3 years in another [1].…”
Section: Discussionmentioning
confidence: 97%
“…The follow-up of our case is considerably longer than previous studies reporting iris lesions. For example, mean follow-up was 2.36 years in one study [6] and up to 3 years in another [1].…”
Section: Discussionmentioning
confidence: 97%
“…The irregular curvature of iris cyst and thin wall has led to the diagnosis of an iris epithelial cyst [11]. It has been shown that the results of imaging with AS-OCT examination are as good as the results of ultrasound biomicroscopy (UBM) examination [12].…”
Section: Discussionmentioning
confidence: 99%
“…The iris cyst develops either from a break in the epithelium or iris stroma; aqueous humor then enters through this port de entrée and creates a space in between where the cyst will grow, eventually reaching the corneal endothelium and resulting in corneal edema [2][3][4][5]. Various surgical procedures for iris cysts have been reported and the result depends on the size of the cyst, the affected area of camera oculi anterior and prompt treatment [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in the surgical management of an iris cyst is to identify the complete extent of the epithelial down growth, and to ensure the removal of the cyst in toto [ 5 ]. If the cyst is ruptured, or part of the cyst wall or associated epithelial downgrowth is left behind, there is a high chance of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These cells in the anterior chamber then grow into a sheet or form a cyst [ 4 ]. Traumatic iris cysts are of two types: the “solid-looking” cyst or pearl cyst has stratified or cubical epithelium lining the cyst wall; the second type is, called the serous cyst, contains straw colored turbid fluid [ 5 ].…”
Section: Introductionmentioning
confidence: 99%